APPLIED SOCIAL PSYCHOLOGY IN INDIAN CONTEXT - Madhok, Sushma (Innovative Research Thoughts, 2017)
Applied social psychology has been around since the dawn of human civilization. Social character of man has piqued the interest of thinkers, artists, and social reformers throughout recorded history. Understanding how individuals interact with each other and conduct their social lives is a major focus of their research. Everything from ancient texts to artefacts to music and poetry has played a role in this project. Evidence of both universality and distinctiveness in diverse civilizations has attracted researchers. People have coexisted as family, community, and nation throughout history, despite the fact that they may not have learnt how to do it peacefully. Since then, human nature has remained virtually unchanged. Many of the problems that ancient social psychology posed seem to be the same ones that modern social psychology is attempting to address. Many new concerns for social psychologists have been raised by the fast social, economic, and political changes that have swept throughout the globe and continents. In order to discover the underlying principles of social interaction, several novel ideas and methodologies are now being created.